2016
DOI: 10.2217/bmm-2016-0163
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Glycocalyx Layer Shedding Following Lung Resection

Abstract: Our pilot study is the first to provide evidence of EGL disruption following lung resection surgery. We hypothesize that EGL disruption is involved in the pathogenesis of post-lung resection acute lung injury. Abstract presentation: This work was presented in a part at the Anaesthetic Research Society Spring Meeting, Royal College of Anaesthetists, London, UK, 22 April 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“… 41 43 Disruption of the endothelial glycocalyx has been demonstrated following surgical trauma or severe injury. 44 46 Consequently, a vicious cycle of postoperative damage to the endothelial glycocalyx and hypoalbuminaemia may contribute to transcapillary albumin leakage and interstitial oedema in patients undergoing hip fracture surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 41 43 Disruption of the endothelial glycocalyx has been demonstrated following surgical trauma or severe injury. 44 46 Consequently, a vicious cycle of postoperative damage to the endothelial glycocalyx and hypoalbuminaemia may contribute to transcapillary albumin leakage and interstitial oedema in patients undergoing hip fracture surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Syndecan-1 has been used as a marker for glycocalyx injury in several clinical reports. 25,27,28 It was recently reported that measurement of syndecan-1 levels in patients with sepsis might be useful for identifying those at high risk of organ dysfunction and mortality as well as those who could benefit from therapies targeted at protecting or restoring the glycocalyx. 27 Therefore, it is surmised that glycocalyx injuries have a relation with human disease.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelial glycocalyx covers the inner surface of the vascular endothelium and regulates leukocyte adhesion [20], thus, leukocytes cannot adhere to endothelial cells covered with glycocalyx, and endothelial glycocalyx injury may occur prior to atherosclerotic changes. Syndecan-1 is a component of the glycocalyx, and its degradation indicates endothelial injury [24,27,28]. In this study, to detect initial endothelial cell injury, we investigated syndecan-1 concentrations in patients who underwent comprehensive medical examinations.…”
Section: Discussionmentioning
confidence: 99%